Weighted Estimates of a Class of Integral Operators with Three Parameters - Ryskul Oinarov; Aigerim Kalybay (Journal of Function Spaces)
We characterize the validity of a Hardy-type inequality with a kernel and three parameters 1<p,q,r<∞ under some conditions on three weight functions u, v, and w.